2020
DOI: 10.14203/ann.bogor.2020.v24.n1.27-34
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic, Antioxidants and Antibacterial Activities of Lactic Acid Bacteria (LAB) from Masin (Fermented Sauce from Sumbawa, West Nusa Tenggara, Indonesia)

Abstract: The study aimed to determine the effectiveness of metabolites from Lactic Acid Bacteria (LAB) derived Masin (fermented sauce from Sumbawa) as antioxidant, antidiabetic, and antibacterial compounds. The LAB isolates were isolated from various strains of Staphylococcus piscifermentan which consisted of Staphylococcus piscifermentans strain CIP103958 (code: 2), strain BULST54 (code: 17), strain SK03 (code: 11), strain ATCC 51136 (code: 34), strain PCM 2409 (code: 28) and strain PU-87 (code: 5). The Metabolites of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…The ability of free radical scavenging by the test sample can be influenced by the extraction method of LAB cells and the concentration of metabolite compounds used (Zhao et al 2015). Manguntungi et al (2020) reported that a high antioxidant activity (71%) of LAB isolated from masin (a fermented sauced) was shown by the highest concentration (500 µg/mL) of masin.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of free radical scavenging by the test sample can be influenced by the extraction method of LAB cells and the concentration of metabolite compounds used (Zhao et al 2015). Manguntungi et al (2020) reported that a high antioxidant activity (71%) of LAB isolated from masin (a fermented sauced) was shown by the highest concentration (500 µg/mL) of masin.…”
Section: Discussionmentioning
confidence: 99%
“…Antidiabetic activity test on roselle flower extract using the modified-glucosidase enzyme inhibition method (Kim et al 2005), as modified by Manguntungi et al (2020). A total of 30 µL of samples at various concentrations were mixed with 36 µL of phosphate buffer pH 6.8 and 17 µL of p-nitrophenyl-α-D-glucopyranoside.…”
Section: Antidiabetic Activity Testmentioning
confidence: 99%
“…Dari data tersebut terlihat bahwa masin menggunakan bioreaktor dengan sistem kontrol suhu memiliki kadar air tertinggi pada hari ketujuh Hal ini disebabkan karena selama proses fermentasi suhu didalam bioreaktor optimum sehingga pertumbuhan bakteri asam laktat optimum dan air merupkan salah satu produk fermentasi. Hasil penlitian ini sesuai dengan penelitian Manguntungi et al (2020) yaitu semakin tinggi kinerja proses fermentasi, menyebakan semakin tinggi kadar air yang dihasilkan. Gambar 6.…”
Section: Hasil Pengujian Produk Fermentasiunclassified